MEMAHAMI MAKNA MUHKAMAT DAN MUTASYABIHAT DALAM AL-QURAN - Yanti, Nova (STAI Hubbulwathan Duri, 2016)
Al-Quran is a guide, a resource and reference for all people. All things related to Al-Quran is deemed noble and commendable. Therefore, the study of Al-Quran still continues because it contains very broad and deep, including problems muhkam and mutasyabih. “Ayat muhkam” is the subject of the Qur'an, and there are some ”ayat mutasyabih” whose meaning is restored to “ayat muhkamat”. Takwil to “ayat mutashabihat” done not only by khalaf generation, but the generation of the Salaf (the first three centuries of Hijra) also did the same thing.